2020
DOI: 10.1186/s13071-020-3893-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative vector competence of North American Lyme disease vectors

Abstract: Background: Understanding the drivers of Lyme disease incidence at broad spatial scales is critical for predicting and mitigating human disease risk. Previous studies have identified vector phenology and behavior, host community composition, and landscape features as drivers of variable Lyme disease risk. However, while the Lyme disease transmission cycles in the eastern and western USA involve different vector species (Ixodes scapularis and Ixodes pacificus, respectively), the role of vector-specific differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…Furthermore, genetic adaptation of pathogen and vector has been shown for I. pacificus and I. scapularis ticks infected with B. burgdorferi s.l. The sympatric vector/pathogen pairing showed significantly higher infection rates as compared to the allopatric vector/pathogen pairings 35 . In addition, first evidence of the genetic stability of TBEV strains of particular TBE natural foci over decades demonstrates the optimal adaptation of a TBEV strain to its vector and host in the respective natural focus (Dobler, unpubl.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, genetic adaptation of pathogen and vector has been shown for I. pacificus and I. scapularis ticks infected with B. burgdorferi s.l. The sympatric vector/pathogen pairing showed significantly higher infection rates as compared to the allopatric vector/pathogen pairings 35 . In addition, first evidence of the genetic stability of TBEV strains of particular TBE natural foci over decades demonstrates the optimal adaptation of a TBEV strain to its vector and host in the respective natural focus (Dobler, unpubl.…”
Section: Discussionmentioning
confidence: 87%
“…species has been analysed. Those studies have shown remarkable differences in vector competence for Ixodes and Borrelia depending on population and species 33 , 35 . Although similar associations of particular tick species, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that dae2 Is modestly limits B. burgdorferi levels in I. scapularis 2 . Paradoxically, B. burgdorferi is a stablyassociated tick microbe that is not cleared by I. scapularis immunity and does not appear to negatively impact tick fitness 13,14 . These observations suggest that Dae2 may promote tick tolerance of B. burgdorferi by preventing excessive proliferation in the vector, similar to what has been observed for host-commensal interactions in other systems 15 .…”
Section: Main Textmentioning
confidence: 99%
“…We previously found that dae2 Is modestly limits B. burgdorferi levels in I. scapularis 2 . Paradoxically, B. burgdorferi is a stablyassociated tick microbe that is not cleared by I. scapularis immunity and does not appear to negatively impact tick fitness 13,14 . These observations suggest that Dae2 may promote tick tolerance of B. burgdorferi by preventing excessive proliferation in the vector, similar to what has been observed for host-commensal interactions in other systems 15 .…”
Section: Main Textmentioning
confidence: 99%